Avaliação de implantação de programa de residência em medicina de família e comunidade de larga escala em capital do nordeste - Ribeiro, Marco Tulio Aguiar Mourao (2009)
The Family´s Health Strategy (ESF) has been implemented for fifteen years in various cities around the country with repercussions in the quality´s attention improvement to population´s health. Notwithstanding there´s a mismatch between the existing necessities to the phisician who work at the ―Atenção Básica à Saúde, or ABS ( Basic Attention to Health), and its more adequate formation. The expansion of jobs on offer at the Family and Community´s Medicine Residence Program (PRMFC/F) did not follow the expansion pace seen at the ESF´s populational covering. An iniquity can be observed in the program´s distribution around the country, with a concentration of them more specifically in the country´s south and southeast. This trend is paradoxical to the distribution of ESF´s teams populational coverage and reflects the absence of a resource direction politics for the need of professionals inside national territory. The Fortaleza Health Department implanted the PRMFC/F, which nowadays has 76 members in its staff. Despite its short period of existence, this program presents some peculiarities: it´s the first one on a large scale implanted in a capital city, concomitantly with the expansion of ESF´s network of services, and with a occupation tax higher than the national average. This recent PRMFC/F implantation process in Fortaleza, Ceará is the theme of this study. After an extensive bibliographical review, a lacuna can be observed at the knowledge reinforcing the relevance of this study. As a main objective, it proposes to evaluate the implantation process of a PRMFC/F on a large scale at a city of large populational presence. Considering the objectives of this investigation, a Case Study will be accomplished, in exploratory character, with imbricated analytical levels, and a combination of Normative Evaluation and Evaluative Research over PRMFC/F implantation components and aspects at Family Health Units in the city of Fortaleza, Ceará. It was found that there was an investment by the city´s government to expand and improve ABS ( Basic Attention to Health) in the city, and that this scenario was favorable to the implantation of the program. It was observed that for the majority of structure, process and result indexes, the PRMFC/F was implanted, and according to normative patterns. Few differences have been observed as to PRMFC/F´s implantation level among the six Fortaleza´s Regional Executive Departments. This study has enabled the formulation of some hypothesis and suggestions for future studies on such a relevant theme to Family and Community Medicine, and Primary Attention to Health´s (Primary Care) current context in Brazil and all over the world.